Pengaruh Pelayanan Pendidikan dan Disiplin Kerja Pegawai terhadap Kepuasan Siswa Di SMPN 2 Gunungguruh Kabupaten Sukabumi - Nanang Rahmatika (LP2M CBI PRESS, 2017)
Education services by schools are services in the form of educational services provided by teachers assisted by education personnel. In order for educational services to run as expected, discipline is needed, especially employee work discipline among educators and education staff.The formulation in this study: (1)Is there an effect of educational services on student satisfaction at SMPN 2Gunungguruh Sukabumi; ; (2) is there anythe effect of employee discipline on student satisfaction studying at SMPN 2Gunungguruh Sukabumi and; (3) To what extent is the influence of education and discipline servicesemployee work on student satisfaction at SMPN 2 Gunungguruh Sukabumi. While the aim is to obtain information abouteverything related to educational services and the level of work disciplinethe following employees are related to the problem of student satisfaction. The approach in this research is survey and the type of research is descriptivequantitative. Data collection techniques with documentation studies, field observations, researchliterature and distributing questionnaires to89 respondents.From the multiple regression equation, the results are that: (1) Every time it occursimprovement in education services oneunits will be followed by an increase in the rate of change in student satisfaction of 0.550; (2) Every time there is an increase in the work discipline of one unit employee, it will be followed by an increase in the level of change in student satisfaction of 0.252. While the partial hypothesis test with